Gelatin enhances the flavor of chicken broth: A perspective on the ability of emulsions to bind volatile compounds. (15th December 2020) - Qi, Jun; Xu, Ying; Xie, Xiao-fei; Zhang, Wen-wen; Wang, Hu-hu; Xu, Xing-lian; Xiong, Guo-yuan
Highlights: Thermally treated gelatin increased the interfacial pressure of the W/O interface. The particle size of emulsions stabilized by pre-heated gelatin reduced. Exogenous addition of gelatin can enhance the flavor strength of chicken broth. Abstract: The mechanism of flavor retention in chicken broth from the perspective of gelatin affecting the flavor-binding ability of emulsions was investigated. Results showed that fat was the important reservoir for aroma compounds in the emulsion. The particle sizes of emulsions significantly decreased with prolonged stewing time of gelatin, which was consistent with the results from confocal laser scanning microscopy and interfacial tension. The ability of pre-heated gelatin emulsions to bind volatile compounds with higher hydrophobicity was enhanced. When 0.1% gelatin was added into chicken broth, the total amount of the main volatile compounds (OAV > 1) increased from 458.83 ng/g to 1218.42 ng/g. In summary, the pre-heated gelatin increased the interfacial pressure of water/oil interface, resulting in a smaller particle size of oil droplets, and these further increased the binding area between oil droplets and flavor compounds. This appears to be the mechanism that gelatin enhances the flavor intensity of chicken broth.